Interplay between the transcription factors acting on the GATA- and GABA-responsive elements of Saccharomyces cerevisiae UGA promoters - Cardillo, Sabrina Beatriz (2012)
γ-Aminobutyric acid (GABA) transport and catabolism in Saccharomyces cerevisiae are subject to a complex transcriptional control that depends on the nutritional status of the cells. The expression of the genes that form the UGA regulon is inducible by GABA and sensitive to nitrogen catabolite repression (NCR). GABA induction of these genes is mediated by Uga3 and Dal81 transcription factors, whereas GATA factors are responsible for NCR. Here, we show how members of the UGA regulon share the activation mechanism. Our results show that both Uga3 and Dal81 interact with UGA genes in a GABA-dependent manner, and that they depend on each other for the interaction with their target promoters and the transcriptional activation. The typical DNA-binding domain Zn(II) 2-Cys 6 of Dal81 is unnecessary for its activity and Uga3 acts as a bridge between Dal81 and DNA. Both the trans-activation activity of the GATA factor Gln3 and the repressive activity of the GATA factor Dal80 are exerted by their interaction with UGA promoters in response to GABA, indicating that Uga3, Dal81, Gln3 and Dal80 all act in concert to induce the expression of UGA genes. So, an interplay between the factors responsible for GABA induction and those responsible for NCR in the regulation of the UGA genes is proposed here. © 2012 SGM.